ChemInform Abstract: Reactivity of Cyclohexene Epoxides Toward Intramolecular Acid‐Catalyzed Cyclizations for the Synthesis of Naturally Occurring Cage Architectures. Issue 31 (11th July 2013) - Abdelkafi, Hajer; Evanno, Laurent; Deville, Alexandre; Dubost, Lionel; Nay, Bastien
Abstract Review: 31 refs.